2015
DOI: 10.3233/ch-141841
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of human red blood cells by a free radical initiator: Effects on rheological properties

Abstract: The main aim of this study was the investigation of the rheological properties of Red Blood Cells (RBCs) obtained from subjects admitted to blood donors, associated with the lipid profile of High-Density Lipoprotein Cholesterol (HDL-C), Low-Density Lipoprotein Cholesterol (LDL-C), Triglyceride (TG) and Total Cholesterol (TOT-C). The deformability index of RBCs was determined by using a Dynamic Stress Rheometer (DSR-500) under oxidative injury induced by 2.2'-azo-bis (2-amidinopropane) dihydrochloride (AAPH). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The ideal composition and stability of the plasma membrane, which is comprised mostly of phospholipids, is crucial to maintain RBC integrity. 22 The lipids that correlate positively with hemolysis in our study are mostly saturated lipids. Due to their structure, saturated lipids increase the rigidity of RBC membranes in which they are incorporated.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The ideal composition and stability of the plasma membrane, which is comprised mostly of phospholipids, is crucial to maintain RBC integrity. 22 The lipids that correlate positively with hemolysis in our study are mostly saturated lipids. Due to their structure, saturated lipids increase the rigidity of RBC membranes in which they are incorporated.…”
Section: Discussionmentioning
confidence: 51%
“…It is not surprising to find a correlation between hemolysis and lipid metabolism and transport. The ideal composition and stability of the plasma membrane, which is composed mostly of phospholipids, is crucial to maintain RBC integrity . The lipids that correlate positively with hemolysis in our study are mostly saturated lipids.…”
Section: Discussionmentioning
confidence: 92%
“…In agreement to our study, a large body of research demonstrates that poor sleep quality affects psychomotor abilities (Ellis, Walczyk, Buboltz, & Felix, 2014), so, Its highly expected that each intervention that is capable of sleep improvement, can increase the attention and concentration. One of the possible mechanisms for improvement of psychomotor performance in training group may be due to augmentation of oxygen uptake, inhibition of vascular inflammatory processes, Rheological alterations in blood (Mazzulla et al, 2015). Gorelick et al (2011) reported that regular strength exercises promote vascularization in the body and enhance essential nutrient supply to the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress had been established as one of the principal causative factors of haematological disorders which include destructions of blood cells leading to secondary complications such as anaemia, leukaemia and thrombocytopenia [1,2]. Moreover, impairment in the functions of endogenous antioxidant systems are known to contribute to the elevation of free radicals and reactive oxygen species leading to oxidative stress.…”
Section: Introductionmentioning
confidence: 99%